Effect of maturity stage and fruit size on the quality of loquat (Eriobotrya japonica Lindl.) cv. Golden Nugget, after canning whole and as a puree - Olaeta J.A.; Undurraga P.; Toledo E. (First international symposium on loquat, 2003)
Fruits from 7 year-old Loquat (Eriobotrya japonica Lindl.) cv. Golden Nugget trees were harvested at three maturity stages, determined by skin colour: dark orange; intense yellow orange; and light yellow orange, and also by fruit size: either fancy, or choice. Fruit was characterized by: soluble solids, pH, total acidity, and sugar per acidity ratio. Fruits were halved and canned in glass jars using heavy syrup, or pureed, cooked and canned in glass jars. Chemical treatments were evaluated after 180 days of storage as described above, and a tasting panel of 16 judges evaluated flavour, sweetness, acidity, texture, general quality and acceptability. An analysis of variance was utilized (randomized block design, four replicates); sensory evaluation was analysed with the Friedman test. The results showed the effect of maturity stage and fruit size on the quality of canned loquat halves. The quality of the canned puree was also affected by the maturity stage of the fruit.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)